Why Does Sovereign Risk Differ for Domestic and Foreign Investors? Evidence from Scandinavia, 19381948 - Daniel Waldenström (Research Institute of Industrial Economics (IFN), 2006)
Recent theoretical models suggest that the costs governments face when defaulting on their domestic and external debt may differ considerably. This paper examines if this proposed cost difference is reflected in sovereign risk spreads across domestic and foreign markets. Specifically, I analyze market yields on Danish government debt in both Denmark and Sweden during 19381948, i.e., a period full of political shocks as well as a wartime segmentation of Scandinavian capital markets. By linking the exogenous wartime shocks to changes in the costs of defaulting on domestic and external sovereign debt, it is found that these costs explain a significant part of the variation in the sovereign risk spread across markets. The result is robust to a multitude of tests and the inclusion of additional yield spread influences such as differences in macroeconomic fluctuations, portfolio allocation opportunities, local risk aversion and microstructure institutions.
Keywords: F34; G15; G18; N20; N24; N44; 330; Sovereign Risk; Investor Heterogeneity; Domestic Debt; External Debt; Market Segmentation; Political Economy; Cliometrics; Internationaler Kredit; Internationaler Finanzmarkt; Öffentliche Anleihe; Anlageverhalten; CAPM; Internationale Marktsegmentierung; Schätzung; Dänemark; Schweden